Low‐intensity extracorporeal shock wave therapy promotes myogenesis through PERK/ATF4 pathway. Issue 2 (1st August 2017) - Wang, Bohan; Zhou, Jun; Banie, Lia; Reed‐Maldonado, Amanda B.; Ning, Hongxiu; Lu, Zhihua; Ruan, Yajun; Zhou, Tie; Wang, Hsun Shuan; Oh, Byung Seok; Wang, Guifang; Qi, Stanley Lei; et al.
Abstract : Aim: Stress urinary incontinence (SUI) is a significant health problem for women. Treatments employing muscle derived stem cells (MDSCs) may be a promising approach to this prevalent, bothersome condition, but these treatments are invasive and require collection of cells from one site for injection into another. It is also unknown whether or not these cells establish themselves and function as muscle cells in the target tissues. Alternatively, low‐intensity extracorporeal shock wave therapy (Li‐ESWT) is non‐invasive and has shown positive outcomes in the treatment of multiple musculoskeletal disorders, but the biological effects responsible for clinical success are not yet well understood. The aim of this study is to explore the possibility of employing Li‐ESWT for activation of MDSCs in situ and to further elucidate the underlying biological effects and mechanisms of action in urethral muscle. Methods: Urethral muscle derived stem cells (uMDSCs) were harvest from Zucker Lean (ZUC‐LEAN) (ZUC‐Leprfa 186) rats and characterized with flow cytometry. Li‐ESWT (0.02 mJ/mm 2, 3 Hz, 200 pulses) and GSK2656157, an inhibitor of PERK pathway, were applied to L6 rat myoblast cells. To assess for myotube formation, we used immunofluorescence staining and western blot analysis in uMDSCs and L6 cells. Results: The results indicate that uMDSCs could form myotubes. Myotube formation was significantly increased by the Li‐ESWT as was the expression of muscle heavy chain (MHC) and myogenic factor 5 (Myf5) in L6 cells in vitro. Li‐ESWT activated protein kinase RNA‐like ER kinase (PERK) pathway by increasing the phosphorylation levels of PERK and eukaryotic initiation factor 2a (eIF2α) and by increasing activating transcription factor 4 (ATF4). In addition, GSK2656157, an inhibitor of PERK, effectively inhibited the myotube formation in L6 rat myoblast cells. Furthermore, GSK2656157 also attenuated myotube formation induced by Li‐ESWT. Conclusion: In conclusion, this experiment reveals that rat uMDSCs can be isolated successfully and can form myotubes in vitro. PERK/ATF4 pathway was involved in myotube formation, and L6 rat myoblast cells were activated by Li‐ESWT to form myotubes. These findings suggest that PERK/ATF4 pathway is activated by Li‐ESWT. This study elucidates one of the biochemical pathways responsible for the clinical improvements seen after Li‐ESWT. It is possible that this information will help to establish Li‐ESWT as an acceptable treatment modality and may help to further refine the use of Li‐ESWT in the clinical practice of medicine.